(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The application of lasers in many fields of technology and medicine is constantly increasing. This causes the development of new physical methods and principles for correct measurement of power, energy, and other parameters of laser sources. In most cases, the correct measurement of the laser power is important because the quality of the processes in which laser sources are used depends on it. In the paper, a comparative analysis of the existing methods for measuring the power and energy of laser radiation of diverse types of laser sources is made. This research aims to help users of laser equipment to choose the right measurement method depending on the laser source.